Strategi Peningkatan Mutu dan Keamanan Produk Olahan Melalui Pelatihan Good Manufacturing Practice (GMP) pada UKM Piyasan Nanggroe Kabupaten Aceh Utara - Khairisma; Fuadi; Puspitaningrum, Rani; Falahuddin; Juanda, Reza; Sinta, Irada; Khairani, Aulia Febri; Mirna; Ayu, Sari (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Community Engagement activities were conducted in Gampong Matang Meunye, Aceh Utara District, with a focus on the development of Micro, Small, and Medium Enterprises (MSMEs) represented by the UKM Piyasan Nanggroe group. This group possesses expertise in producing high-quality dried bananas, referred to as "pisang gintong," and aspires to scale up production extensively. The objective of this Community Engagement was to provide support in enhancing production and business legality, particularly in the realm of business management, encompassing business motivation, financial recording, and digital marketing. Furthermore, this endeavor aimed to elevate product quality by implementing Good Manufacturing Practices (GMP) with hygienic and efficient standards and introducing processed banana products using state-of-the-art processing technology that is more hygienic and healthier while leveraging local resources. The implementation of the activities comprised three stages: preparation, program execution, and evaluation. The preparation phase encompassed pre-surveys, team formation, proposal development and submission, team and partner coordination, and the preparation of training materials. The program execution stage involved disseminating information and conducting discussions to impart knowledge in business management, digital marketing, and GMP practices. The evaluation and reporting phase ensured the success of the program. After the program, it is anticipated that MSME entrepreneurs within the UKM Piyasan Nanggroe group will experience increased production capacity, a better understanding of the importance of sound financial record-keeping, the implementation of marketing strategies through labels (Halal and branding), and the adoption of hygienic standard processing technology. This article aims to provide practical guidance for MSME entrepreneurs in enhancing their quality and competitiveness.